INTERNATIONALIZATION AGENDA: LANGUAGE AS A BARRIER - Rawdhah Paiz (Proceedings Education and Language International Conference, 2017)
Internationalization is an important feature of a reputable university. In their mission to internationalize the campus population, universities often admit students from other countries into their programmes. This does not come without challenges especially in situation where students are different in their language backgrounds. The situation is more challenging when the language of instruction is also a foreign language to the local students. This study was conducted to find the reasons for the difficulties faced when communicating with each other between the local and international students at a public university in Malaysia. The students were observed and interviewed for the study. The difficulties in communicating were attributed to many reasons, which include native language interference, use of local variety of the language and students’ lack of confidence in using the language.Keywords: communication, interaction, internationalization